Penerapan Metode Fuzzy Tsukamoto Untuk Penentuan Negara Penyuplai Beras Pada Perusahaan Logistik - Eneng Siti Nurjanah; Irmayansyah Irmayansyah; Leny Tritanto Ningrum (SKANIKA: Sistem Komputer dan Teknik Informatika, 2025)
Inaccuracy in determining rice supplier countries is currently a complex issue. This situation is influenced by various factors that are often difficult to predict and have the potential to suddenly change rice supply conditions. Extreme climate change and unexpected fluctuations in domestic demand can also influence decisions regarding rice supplier countries. Under these conditions, logistics companies require a more adaptive and responsive supply strategy to changes in rice availability. Selecting the right supplier country plays a crucial role in the operational efficiency and business sustainability of logistics companies. This study aims to apply the Fuzzy Tsukamoto method as a supporting tool in the process of determining rice supplier countries for logistics companies. The Tsukamoto method is used to calculate rice supplier categories by utilizing three input variables: import quantity, demand quantity, and rice quality. Meanwhile, the output variables are classified into three categories: low, medium, and high. The accuracy of the rice supplier country grouping results using the Tsukamoto method has been tested and obtained an accuracy value of 73.33%. The developed application prototype has also undergone user feasibility testing using the Post-Study System Usability Questionnaire (PSSUQ) instrument and resulted in a feasibility level of 91.1%.